INTEGRASI PROGRAM TAHFIZH AL-QURAN DENGAN HIGH ORDER THINGKING SKILLS (HOTS) MODEL DI SEKOLAH DASAR - Enung Nugraha (Jurnal keilmuan dan Kependidikan dasar, 2020)
The advancement of civilization requires fundamental innovation and revolution, with creating highly engineered resources, both from an increasing work system efficiently without much use of human labor. This challenge must prepare human resources through the leading education system without leaving the faithful identity. Tahfizh Al-Qur’an is one of religious programs that increase concentration and student learning outcomes. HOTS model approach an important role in achieving it with integration. The aim of this study is finding how the integration of tahfizh Al-Qur’an in high order thinking skills (HOTS) learning model in elementary schools. The method used is the literature study approach. The tahfizh program at elementary schools is part of religious and character education for students it can memorize, deepen their meaning, empathy, internalize and habituate at school and home. The teachers can apply high order thinking skills learning model, not only evaluating the memorization of the Qur'an but until students act to do something even become habituated to themselves. The integration of tahfizh Al-Qur'an program in HOTS learning model in elementry schools is important pursuing by teachers in schools and guiding by parents at home so that habituation in addition to increasing concentration also fosters empathy for action.